Histology and Immunohistochemistry of Adipose Tissue: A Scoping Review on Staining Methods and Their Informative Value - Tom Schimanski; Rafael Loucas; Marios Loucas; Oliver Felthaus; Vanessa Brébant; Silvan Klein; Alexandra Anker; Konstantin Frank; Andreas Siegmund; Andrea Pagani; Sebastian Geis; Sophia Theresa Diesch; et al. (Cells, 2025)
Background: Histological and immunohistochemical analyses of adipose tissue are essential for evaluating the quality and functionality of lipoaspirates in regenerative medicine and fat grafting procedures. These methods provide insights into tissue viability, cellular subtypes, and extracellular matrix (ECM) composition—all factors influencing graft retention and clinical outcomes. Purpose: This scoping review aims to summarize the most commonly used staining methods and their applications in the histology and immunohistochemistry of adipose tissue. By exploring qualitative and quantitative markers, we seek to guide researchers in selecting the appropriate methodologies for addressing experimental and translational research. Methods: A systematic search was conducted using PubMed, Ovid, and the Cochrane Library databases from inception to 2024, employing Boolean operators (“lipoaspirate” OR “fat graft” OR “gauze rolling” OR “decantation” OR “coleman fat” OR “celt” OR “nanofat” OR “lipofilling” OR “human fat” AND “histol*”). Studies were included if they utilized histology or immunohistochemistry on undigested human adipose tissue or its derivatives. The inclusion criteria focused on peer-reviewed, English-language studies reporting quantitative and qualitative data on adipose tissue markers. Results: Out of 166 studies analyzed, hematoxylin–eosin (H&E) was the most frequently employed histological stain (152 studies), followed by Masson Trichrome and Sudan III. Immunohistochemical markers such as CD31, CD34, and perilipin were extensively used to distinguish stromal vascular fraction (SVF) cells, adipocytes, and inflammatory processes. Studies employing semiquantitative scoring demonstrated enhanced comparability, particularly for fibrosis, necrosis, and oil cyst evaluation. Quantitative analyses focused on SVF cell density, mature adipocyte integrity, and ECM composition. Methodological inconsistencies, particularly in preparation protocols, were observed in 25 studies. Conclusions: This review highlights the critical role of histological and immunohistochemical methods in adipose tissue research. H&E staining remains the cornerstone for general tissue evaluation in the clinical context, while specialized stains and immunohistochemical markers allow for detailed analyses of specific cellular and ECM components in experimental research. Standardizing preparation and evaluation protocols will enhance interstudy comparability and support advancements in adipose tissue-based therapies.